FORMULASI HUKUM DAN PENTINGNYA JAMINAN KEPASTIAN HUKUM PRODUK PANGAN HALAL DALAM HUKUM NASIONAL - Sofyan, KN (Universitas Islam Negeri Raden Fatah Palembang, 2015)
Abstract: The Food Act No.18 of 2012 is in the government'sdevelopment efforts of food to meet the basic needs of theIndonesian people in a fair and equitable based onindependence and not contrary to the religion, beliefs and,cultur of society. Related to food safety hazards includingdangerous category of